Connecting Tradition with Innovation: The Impact of WordWall on Learning Outcomes in Fiqh Studies - Maisuroh, Siti; Aisyah, Nur; Sanjani, M. Aqil Fahmi (FONDATIA, 2024)
This study investigates the effect of AI-based Word Walls on the learning outcomes of Fiqh students at MIN 1 Probolinggo. Highlighting the role of innovative learning tools in improving student achievement, the research utilizes a quantitative approach with a quasi-experimental design, involving 42 first-grade students from MIN 1 Probolinggo. Over four weeks, the experimental group engaged with Word Walls, while the control group continued with traditional teaching methods. The results showed a significance value (Sig.) (2-tailed) of 0.000 for Pair 1 and 0.000 for Pair 2, both below 0.05, indicating a substantial effect of Word Wall media on student learning outcomes. Furthermore, the independent t-test revealed a Sig. value (2-tailed) of 0.000, underscoring a significant difference in average learning outcomes between the Word Wall media and conventional methods. In conclusion, the use of AI-based Word Walls substantially improves learning outcomes in Fiqh subjects at MIN 1 Probolinggo.